THE NATURAL HERITAGE OF LIBRAZHDâ€ŸS DISTRICT, IN FUNCTION OF THE STABLE DEVELOPMENT - LirÃ«za, Qamil (European Scientific Journal, ESJ, 2014)
During the treatment of this paper it is aimed the accurate characterization of natural objects that constitute the natural heritage of this region, as well as the proposals for new monuments. In this article it is conducted a genuine scientific work for the analysis of these monuments and the values associated with them. The basic method that is used in the treatment of this paper has been the one of direct field observations, analyzing these aspects; their physical condition, size, prognosis and photography. The paper has scientific value to researchers in the field of geography and local authorities. The main part in the paper is occupied by the results of the performed work in the following areas: The assessment of the natural conditions of this district, in function ofthe natural monuments. The classification of natural monuments; geomonuments, bio and hidromonuments. The physical analysis of the declared monuments,explaining their current situation and future trend.Their association with different views. Proposals for new natural monuments, for those objects that meet the criteria of being such. All these proposed monuments, are analyzed by the natural aspect, and accompanied by photos. At the end of this paper are given the conclusions, noting that the natural heritage of this district is a national asset. There are given some recommendations such as; their defence is responsibility of the state and of all the public opinion. Their good management requires strong legal measures in order to preserve these values.